Design of the Extraction Process for Terpenes and Other Volatiles from Allspice by Solid-Phase Microextraction and Hydrodistillation - Bajer, Tomáš; Ligor, Magdalena; Ligor, Tomasz; Buszewski, Boguslaw (My University, 2016)
Methods for the separation and determination of terpenes (mono- and sesqui-) and phenylpropanoids such as eugenol and methyleugenol from samples of allspice berries have been developed. Chromatographic analyses of isolated groups of compounds were carried out by means of gas chromatography coupled with mass spectrometry. A comparison of various types of solid-phase microextraction fibers was performed. The highest yields of terpenes were extracted by polydimethylsiloxane and divinylbenzene/ Carboxen/polydimethylsiloxane fibers (almost the same for these two fibers), approximately twice as much as by Carbowax/divinylbenzene fiber. The highest amounts of monoterpenes were extracted by divinylbenzene/Carboxen/polydimethylsiloxane fiber, and the highest amounts of sesquiterpenes were extracted by polydimethylsiloxane fiber. Moreover, the effect of water addition on extraction yields as well as time and temperature of extraction were tested. Aroma profiles of extracts obtained by solid-phasemicroextraction and essential oil obtained by hydrodistillation of allspice berries were compared. The aroma profile of the divinylbenzene/Carboxen/polydimethylsiloxane fiber extract was similar to the aroma profile of essential oil. Particular characteristics of volatile allspice matters were presented. The linear retention indices for each compound were calculated.
Návrh extrakčního procesu pro terpeny a další těkavé sloučeniny nového koření pomocí mikroextrakce tuhou fází a hydrodestilace
Keywords: Allspice; Essential Oils; Gas Chromatography with Mass Spectrometry; Solid-Phase Microextraction; Terpenes; Nové Koření; Silice; Plynová Chromatografie s Hmotnostní Detekcí; Mikroextrakce Tuhou Fází; Terpeny